Asuhan Keperawatan Pada Ny. W Keluarga Tn.K Dengan Gangguan Sistem Endokrin: Diabetes Melitus Di Desa Kutayu RT 05 RW 05 Kecamatan Tonjong Kabupaten Brebes - Naela Akmala Ananti; Tati Karyawati; Arisnawati Arisnawati (Lembaga Pengembangan Kinerja Dosen, 2023)
Diabetes Mellitus is a metabolic disorder that occurs chronically or chronically because the body does not have enough insulin hormone due to interference with insulin secretion, the insulin hormone does not work as it should or both (Hendry et al., 2023). The International Diabetes Mellitus Federation (IDF) organization estimates that at least 463 million people aged 20-79 years in the world suffered from diabetes mellitus in 2019 or equivalent to a prevalence rate of 9.3% of the total population of the same age. Based on gender, IDF estimates that the prevalence of diabetes in 2019 is 9% in women and 9.65% in men. (Indonesian Ministry of Health, 2020). Prevalence data from the Indonesian Ministry of Health in 2013-2018, there are 4 provinces with the highest prevalence, namely DKI Jakarta 3.4% East Kalimantan 3.1% In Yogyakarta 3.1%, North Sulawesi 3% and Central Java 2.1% ( Research and Development Agency, Republic of Indonesia Ministry of Health, 2019).